2021
DOI: 10.14366/usg.20085
|View full text |Cite
|
Sign up to set email alerts
|

Current status of deep learning applications in abdominal ultrasonography

Abstract: Ultrasonography. 2020 Sep 2. Epub ahead of print Deep learning is one of the most popular artificial intelligence techniques used in the medical field. Although it is at an early stage compared to deep learning analyses of computed tomography or magnetic resonance imaging, studies applying deep learning to ultrasound imaging have been actively conducted. This review analyzes recent studies that applied deep learning to ultrasound imaging of various abdominal organs and explains the challenges encountered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…On the other hand, DL has recently emerged as the leading machine learning tool in various research fields. It is one of the most popular artificial intelligence techniques used in the medical field, especially for image and video processing, thus numerous studies applying deep learning to ultrasound/CEUS imaging have been actively conducted [ 16 , 17 ]. The current section reviews CEUS based DL approaches for medical investigation, in general, and for FLL diagnosis, in particular.…”
Section: State Of the Artmentioning
confidence: 99%
“…On the other hand, DL has recently emerged as the leading machine learning tool in various research fields. It is one of the most popular artificial intelligence techniques used in the medical field, especially for image and video processing, thus numerous studies applying deep learning to ultrasound/CEUS imaging have been actively conducted [ 16 , 17 ]. The current section reviews CEUS based DL approaches for medical investigation, in general, and for FLL diagnosis, in particular.…”
Section: State Of the Artmentioning
confidence: 99%
“…At present, diagnostic imaging has considerable potential in the diagnosis of and intervention into abdominal pathologies, and was recently also supported by integration with artificial intelligence methods [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The suggestion of ischemic colitis based on imaging findings can permit early diagnosis and prompt therapy, which is essential for a successful outcome [51].…”
Section: Imagingmentioning
confidence: 99%
“…Artificial intelligence, such as deep learning algorithms, is gaining extensive attention in medical imaging and studies applying deep learning to US are being actively conducted, mainly in the field of diffuse liver disease, especially hepatic fibrosis and steatosis evaluation[ 70 , 71 ]. In a recent study of 3446 patients a deep convolutional neural network showed high accuracy in the assessment of METAVIR score using US images and achieved better performance than that of radiologists in the diagnosis of cirrhosis[ 72 ].…”
Section: Artificial Intelligence and Radiomic Ultrasound Analysismentioning
confidence: 99%